Prosthetic management of severely resorbed mandibular ridge using neutral zone technique in complete dentures: a case report - Wilson, Teena; Ravichandran, R; Harsha Kumar, K; Nair, Vivek V (International Journal of Dental Materials, 2022)
Any prosthodontic procedure aims to restore a patient’s function, contours, aesthetics, speech, and health to normal. In traditional complete dentures, achieving optimal denture stability is always found to be a challenge. This is often exacerbated in resorbed mandibular ridges. Therefore, this article describes a strategy for enhancing the retention of mandibular complete dentures for individuals with an extremely resorbed ridge. A patient reported to the department of prosthodontics with a chief complaint of loose dentures and wanted to get them replaced. A complete clinical examination was carried out which revealed severely resorbed mandibular ridge. After a complete evaluation, prosthetic rehabilitation with a complete denture using the neutral zone technique was panned. The complete denture was made and delivered to the patient was superior in terms of stability, function and aesthetics. The clinician should understand the advantages of the neutral zone technique and implement it in clinical practice so that a prosthesis that is functionally, physiologically and psychologically acceptable to the patient can be delivered.